PENGARUH KEMAMPUAN MANAJERIAL TERHADAP TINGKAT PROFITABILITAS PADA PT. BANK SULSELBAR CABANG MAKASSAR - Abdul Khalik (Jurnal Bisnis dan Kewirausahaan, 2019)
This study aims to discuss the importance of managerial on the level of profitability at PT Bank Sulselbar Makassar Branch. The analysis method used in this study uses "Simple Regression Analysis to study the relationship of independent variables to using variables. Research Results on managerial capabilities have a positive and significant effect on the level of profits at Bank Sulselbar Makassar Branch.